Tafsir dan Pemasyarakatan Al-Qur'an - Muhammad Quraish Shihab (Lajnah Pentashihan Mushaf Al-Qur'an, 2008)
This writing is an effort to offer how to socialize the understanding of Qur'anic exegesis (tafsir). It starts from the mapping the needs of society toward Qur'anic exegesis, the method being used, as well as the obstacles being faced either internal obstacles such as the ideas or the thoughts of the exegete or external obstacles such as the intellectual level of society in accepting that thought.